Phase change microcapsule for high-temperature and ultra-high-temperature drilling fluid and preparation method and application thereof

CN122941375APending Publication Date: 2026-10-20CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611196186.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但是在高温深井钻探过程中,高温环境会造成钻井液处理剂高温失效、钻井液体系高温失稳等问题,从而引发严重的工程作业问题,主要体现在以下几个方面:(1)降滤失剂、增粘剂等处理剂在高温下分子结构破坏、基团变异或脱附,导致功能失效;(2)高温导致流变性失控(如黏切异常)、滤失量剧增、重晶石等固相沉降,以及油基钻井液乳化体系破坏等;(3)抗温抗盐极限不足:传统水基钻井液抗温上限约200℃,难以满足高温超高温地层的钻井作业需求

Benefits of technology

(1)本发明采用熔融盐作为相变芯材,通过芯材组分的调节,实现了在180℃至255℃的宽温区内对相变温度的灵活调控,能够精准匹配不同深度地层的实际温度需求。并通过构建无机耐高温包覆层制备得到相变微胶囊,相较于传统有机相变材料微胶囊,具有更高的相变温度和热稳定性,拓宽了相变材料在深井、超深井钻井液体系中的应用范围。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of drilling fluid technology, specifically relating to a phase change microcapsule for high-temperature and ultra-high-temperature drilling fluids, its preparation method, and its application. This invention uses molten salt as the phase change core material. By adjusting the core material composition and / or adding thermally conductive materials, flexible control of the phase change temperature is achieved within a wide temperature range of 180℃ to 255℃, precisely matching the actual temperature requirements of formations at different depths. Furthermore, phase change microcapsules are prepared by constructing an inorganic high-temperature resistant coating layer. Compared to traditional organic phase change material microcapsules, these microcapsules exhibit higher phase change temperatures and thermal stability, broadening the application range of phase change materials in deep and ultra-deep well drilling fluid systems. This invention uses an in-situ coating method to prepare phase change microcapsules, which is simple to prepare, operates under mild conditions, and achieves ideal particle size distribution. This reduces preparation difficulty and improves production efficiency, paving the way for its engineering application in ultra-deep well drilling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of drilling fluid technology, specifically relating to a phase change microcapsule for high-temperature and ultra-high-temperature drilling fluids, its preparation method, and its application. Background Technology

[0002] Oil and gas exploration and development is accelerating its extension into deep and ultra-deep formations. However, during high-temperature deep well drilling, the high-temperature environment can cause problems such as high-temperature failure of drilling fluid treatment agents and high-temperature instability of the drilling fluid system, which can lead to serious engineering operation problems. These problems are mainly reflected in the following aspects: (1) The molecular structure of treatment agents such as filtration loss reducers and viscosifiers is destroyed, groups are mutated or desorbed at high temperatures, resulting in functional failure; (2) High temperature leads to uncontrolled rheology (such as abnormal viscosity and shear), a sharp increase in filtration loss, solid phase sedimentation such as barite, and damage to the oil-based drilling fluid emulsion system; (3) Insufficient temperature and salt resistance limits: the upper limit of temperature resistance of traditional water-based drilling fluid is about 200℃, which is difficult to meet the drilling operation requirements of high-temperature and ultra-high-temperature formations. Therefore, how to achieve effective cooling and thermal management of drilling fluid during wellbore circulation, as well as safe and efficient development, has become one of the core technical challenges facing safe and efficient drilling in ultra-deep formations.

[0003] To address the aforementioned issues, existing technologies primarily seek solutions from two levels: active surface cooling and downhole thermal management. Surface cooling methods reduce the inlet temperature by installing cooling devices in the drilling fluid circulation process on the surface, indirectly suppressing wellbore temperature rise. However, this method involves large equipment investments, high energy consumption, and limited cooling effectiveness for ultra-deep wells, failing to fundamentally solve the problem of high bottom-hole temperatures. In recent years, the idea of ​​utilizing the latent heat storage properties of phase change materials (PCMs) to achieve active downhole temperature control has attracted widespread attention. PCMs can absorb or release a large amount of latent heat near their phase change temperature while maintaining a constant temperature. Introducing them into the drilling fluid system holds promise for achieving thermal regulation in the high-temperature section of the wellbore.

[0004] Following this line of thought, existing research has attempted to introduce phase change materials (PCMs) into drilling fluid systems to achieve active downhole temperature control by utilizing the heat absorption of PCMs. For example, Chinese patent CN111545142A discloses a high-temperature PCM isothermal microcapsule and an active temperature-controlled high-temperature drilling fluid system. This technology uses paraffin-based PCMs as the core material and encapsulates them with polymer wall materials, utilizing the heat absorption of PCMs during drilling fluid circulation to reduce downhole temperature. However, due to the limited temperature resistance of paraffin-based PCMs, their PCM temperatures are insufficient to meet the application requirements of deep and ultra-deep wells in environments with temperatures exceeding 200 °C. Chinese patent CN117701255A further utilizes a molten salt blend of sodium nitrate and potassium nitrate as the PCM core material, and uses tetraethyl orthosilicate (TEOS) as the silicon source to encapsulate a silica shell using a sol-gel method, preparing PCM capsules with stronger temperature resistance. However, this approach involves multiple emulsification, coating, and post-processing steps, resulting in a complex preparation process with stringent process control requirements, which is not conducive to large-scale engineering applications. Some studies have used erythritol (phase transition temperature approximately 120 °C, latent heat exceeding 235 J / g) as the phase change core material and polymers such as polysulfone as the shell material to construct microcapsules, achieving excellent thermal storage performance, but the phase change temperature remains limited to the mid-temperature range. In recent years, research on phase change microcapsules based on the synergistic modification of biochar frameworks and supramolecular structures has also increased the operating temperature, but long-term stability in ultra-high temperature drilling environments exceeding 200 °C remains to be verified.

[0005] In summary, existing drilling fluid temperature-controlled phase change materials still have the following shortcomings: Firstly, the temperature resistance range of existing phase change materials is limited, making it difficult to meet the extreme operating conditions of deep and ultra-deep wells, which can reach temperatures above 200 ℃ or even 250 ℃. Secondly, existing microcapsule preparation processes are generally complex, involving multiple steps, resulting in low synthesis efficiency and high cost, which is not conducive to large-scale preparation and engineering applications. Therefore, developing a phase change microcapsule with adjustable phase change temperature, suitable for high-temperature or ultra-high-temperature drilling environments, and with a simpler and more efficient preparation process, as well as its preparation method, has significant engineering application value. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a phase change microcapsule for high temperature and ultra-high temperature drilling fluid, its preparation method and application. Molten salt is used as the phase change core material and inorganic high temperature resistant material is used as the coating layer. Through oil-in-water emulsification and interfacial polymerization coating process, a dense inorganic shell layer is formed on the surface of molten salt to meet the requirements of ultra-deep wells.

[0007] The technical solution adopted is as follows: A method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids includes the following steps: S1. Molten salt phase change core material and hydrophilic emulsifier are added to deionized water, the pH value is adjusted, and the mixture is mixed to form an aqueous phase containing the molten salt phase change core material; S2 adds a lipophilic emulsifier to the organic phase and mixes them to form an organic phase containing the lipophilic emulsifier; S3 mixes the aqueous phase and the organic phase and emulsifies them to form a water-in-oil emulsion; S4. The wall material is added to the water-in-oil emulsion, and a high-temperature resistant coating layer is formed on the outer surface of the molten salt phase change core material by interfacial polymerization to obtain coated phase change microcapsules. S5 separates, washes, and dries the encapsulated phase change microcapsules to obtain phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids.

[0008] Preferably, in step S1, the molten salt phase change core material includes one or more of potassium nitrate, sodium nitrate, lithium nitrate, sodium chloride, barium nitrate, sodium sulfate, and halide salts; The hydrophilic emulsifier includes one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, Tween-40, and Tween-80; The mixing conditions are: water bath at 20–50 °C, stirring for 15–30 minutes, and a rotation speed of 200–500 r / min. The mass ratio of the hydrophilic emulsifier to the molten salt phase change core material is 1:15 to 30.

[0009] Preferably, step S1 further includes adding a thermally conductive material to the aqueous phase; the thermally conductive material is any one or a mixture of MgO, BN or AlN; the mass ratio of the thermally conductive material to the molten salt is 1:10 to 20.

[0010] Preferably, in step S2, the organic phase is liquid paraffin or white oil; The lipophilic emulsifier includes one or more of glyceryl monostearate, glyceryl monooleate, Span-40, and Span-80.

[0011] Preferably, in step S2, the mass ratio of the lipophilic emulsifier to the organic phase is 1:5 to 10; the stirring temperature is 30 to 65°C; the stirring time is 20 to 40 minutes; and the stirring speed is 400 to 600 r / min.

[0012] Preferably, in step S3, the emulsification conditions are ultrasonic emulsification in an ultrasonic cleaner for 20 to 30 minutes, and the emulsification stirring rate is 1000 to 5000 r·min−1.

[0013] Preferably, in step S4, the wall material is a mixture of silicon source precursors; The reaction was carried out in a constant temperature water bath at 40–70°C, and stirred at a magnetic stirring speed of 500–1000 r / min for 20–30 minutes to form a uniformly dispersed system. The pH value of the reaction system is 8-13, preferably 8-9; the reaction time is 8-16 h; wherein, the pH adjuster used is one or more of ammonia, sodium hydroxide, hydrochloric acid, and triethanolamine; Preferably, the silicon source precursor mixture is a mixture of tetraethyl orthosilicate (TEOS) and 3-aminopropyltrimethoxysilane (APTMS, a silane coupling agent with organic functional groups, which contains both silanoxy groups that can react with inorganic substances and highly active organic amino groups). Through hydrolysis and condensation reactions, a strong and dense silica network is formed, and the core-to-wall ratio is 1:0.5 to 2.

[0014] Preferably, in step S5, the washing process involves alternating between deionized water and anhydrous ethanol 2-3 times, and the drying temperature is 100-120°C.

[0015] A phase change microcapsule for high-temperature and ultra-high-temperature drilling fluid includes a molten salt phase change core material and an inorganic wall material layer covering the outer surface of the molten salt phase change core material, wherein the core material is a high-temperature or ultra-high-temperature phase change core material with adjustable phase change temperature. The phase change microcapsules have a phase change temperature of 180–255°C and a core material encapsulation rate of 50–60%.

[0016] The application of a phase change microcapsule for high-temperature and ultra-high-temperature drilling fluids in high-temperature water-based drilling fluids, wherein the drilling fluid comprises 5 to 12 parts of the phase change microcapsule; When the phase change microcapsules are added to the drilling fluid system, they undergo phase change and heat absorption when they reach their phase change temperature, thereby reducing the rate of temperature rise in the drilling fluid. The high-temperature and ultra-high-temperature drilling fluids are suitable for downhole environments of 180–255°C.

[0017] Adding a small amount of thermally conductive material to the surface of microcapsules can improve their thermal conductivity. Since SiO2 has high thermal conductivity, when the core material is coated with a shell material, the thermal conductivity of the microcapsules can be improved to some extent. Adding a small amount of thermally conductive material significantly increases the thermal conductivity of the microcapsules.

[0018] Compared with existing technologies, the present invention has the following advantages: (1) This invention uses molten salt as the phase change core material. By adjusting the composition of the core material, the phase change temperature can be flexibly controlled within a wide temperature range of 180℃ to 255℃, which can accurately match the actual temperature requirements of different formation depths. Furthermore, phase change microcapsules are prepared by constructing an inorganic high-temperature resistant coating layer. Compared with traditional organic phase change material microcapsules, they have higher phase change temperature and thermal stability, thus broadening the application range of phase change materials in deep and ultra-deep well drilling fluid systems.

[0019] (2) This invention endows the microcapsules with a high latent heat of phase change by combining an oil-in-water emulsion system with an in-situ coating reaction. At the same time, the dense coating of inorganic wall material with a high coating rate (50% to 60%) effectively isolates the phase change core material from the drilling fluid system, improves the structural stability of the microcapsules, reduces the risk of core material leakage under high temperature conditions, and ensures that the core material is not easily lost under the harsh working conditions of long-term, high-temperature cycling. The phase change microcapsules can continuously and stably perform the function of heat absorption and cooling, and greatly improve the service life.

[0020] (3) The phase change microcapsules prepared by the present invention are applied to the ultra-high temperature drilling fluid system. When the downhole temperature reaches the phase change temperature range, they can absorb heat through phase change, reduce the rate of temperature rise of drilling fluid, reduce the thermal degradation rate of thickeners, etc., and synergistically ensure the overall high temperature stability of the drilling fluid system and improve the stability of drilling fluid in ultra-high temperature environment.

[0021] (4) The present invention uses an in-situ coating method to prepare phase change microcapsules. There is no need for a complex multi-step assembly process. The high temperature resistant microcapsule structure can be formed simply through emulsification dispersion and coating reaction. The preparation process is simple and the operating conditions are mild. It can achieve an ideal particle size distribution, which is conducive to reducing the preparation difficulty and improving production efficiency, paving the way for its engineering application in ultra-deep well drilling. Attached Figure Description

[0022] Figure 1 This is a flowchart of the microcapsule synthesis process of the present invention.

[0023] Figure 2 This is a schematic diagram illustrating the synthesis principle of the inorganic wall material of this invention.

[0024] Figure 3 Fourier transform infrared spectra of GW-3, SiO2 and core material prepared in Example 3.

[0025] Figure 4 The XRD patterns of GW-3, SiO2 and core material prepared in Example 3 are shown.

[0026] Figure 5 This is a comparison of the encapsulation rates of phase change microcapsules at different pH values ​​according to the present invention.

[0027] Figure 6 This invention provides a comparison of the encapsulation rates of phase change microcapsules with different core-to-wall ratios.

[0028] Figure 7 This invention provides a comparison of the shear strength of phase change microcapsules with different core-to-wall ratios. Detailed Implementation

[0029] The accompanying drawings are for illustrative purposes only; the illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention.

[0030] Halides (L) and LiNO3 (LN) were purchased from Sinopharm Chemical Reagent Co., Ltd., and were of analytical grade. Other drugs not specifically designated were available through regular commercial channels.

[0031] The technical solutions of this application are described in detail below with reference to the embodiments, but the present invention is not limited to these embodiments.

[0032] Example 1 like Figure 1 As shown, the specific steps of a method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids are as follows: In a constant temperature water bath at 40℃, 12g of molten salt (composed of lithium nitrate and sodium nitrate in a mass ratio of 54:46) and 0.5g of Tween-80 were added to 30mL of deionized water and stirred at 600r / min for 30 minutes to obtain the aqueous phase. 4g of Span-40 was added to 60mL of liquid paraffin and stirred thoroughly at 500r / min for approximately 30 minutes to obtain the oil phase. The aqueous phase was then added to the oil phase, and the mixture was ultrasonically emulsified for 30 minutes to form a stable W / O emulsion. 12 mL of ethyl silicate was added to the water-in-oil emulsion and stirred for 20 minutes at a magnetic stirring speed of 700 r / min in a constant temperature water bath at 50 °C to form a uniformly dispersed system. Then, ammonia water was added dropwise to adjust the pH to 11, and stirring was continued for 10 hours. After the reaction was complete, the product was washed three times alternately with deionized water and anhydrous ethanol. Finally, the product was dried at 100 °C. The resulting high-temperature water-based drilling fluid was labeled GW-1 using phase change microcapsules with a phase change temperature of 195 °C.

[0033] like Figure 2 As shown, during the synthesis of phase change microcapsules, an emulsifier disperses the aqueous solution in the organic phase, forming a uniform W / O emulsion. At this point, the silicon source precursor mixture added to the system, including TEOS, rapidly distributes itself at the W / O interface due to its lipophilic properties. The silicon atoms in TEOS are chemically bonded to four ethoxy groups (-OCH2CH3), resulting in stable chemical properties. When OH⁻ is present in the system, it attacks the silicon nucleus, changing its charge to negative. This causes the electron cloud to shift towards the ethoxy group, lowering the Si-O bond energy and ultimately leading to nucleophilic substitution. Once all four ethoxy groups are replaced by -OH, Si(OH)4 and ethanol are generated in the system. This process is the hydrolysis of TEOS.

[0034] In the system, the Si-OH groups generated by the hydrolysis of TEOS undergo self-condensation reactions with each other or hinged condensation reactions with unhydrolyzed Si-OC2H5 groups, ultimately forming a three-dimensional SiO2 network framework. Similar to TEOS, the later-added APTMS tends to aggregate at the oil-water interface. The amino groups on APTMS enable it to diffuse from the oil phase into the aqueous phase, generating OH⁻ in the water. This promotes the co-hydrolysis and condensation reactions of APTMS and TEOS, initially forming a SiO2 shell at the W / O interface. At this point, TEOS and APTMS can penetrate from the oil phase into the aqueous phase through this shell, continuously undergoing hydrolysis and condensation reactions to increase the thickness of the SiO2 shell on the water droplet surface until the precursor can no longer penetrate the SiO2 shell, at which point the shell growth stops and the reaction ends.

[0035] Example 2 The preparation of a phase change microcapsule for high-temperature drilling fluid includes the following steps: At room temperature, 8 g of molten salt (composed of sodium nitrate and potassium nitrate in a mass ratio of 46:54) and 0.8 g of Tween-40 were added to 20 mL of deionized water and stirred at 500 rpm for 40 minutes to obtain the aqueous phase. 5 g of Span-80 was added to 50 mL of liquid paraffin and stirred thoroughly at 700 rpm for approximately 30 minutes to obtain the oil phase. The aqueous phase was then added to the oil phase, and the mixture was ultrasonically emulsified for 30 minutes to form a stable W / O emulsion. 8 mL of ethyl silicate was added to a water-in-oil emulsion and stirred for 20 minutes at 800 r / min in a constant temperature water bath at 60°C to form a uniformly dispersed system. Then, ammonia was added dropwise to adjust the pH to 10, and stirring was continued for 12 hours. After the reaction was complete, the product was washed three times alternately with deionized water and anhydrous ethanol. Finally, the product was dried at 120°C to prepare high-temperature water-based drilling fluid phase change microcapsules, denoted as GW-2, with a phase change temperature of 225°C.

[0036] Application Example 1 The GW-1 prepared in Example 1 was added as a temperature control additive to a high-temperature water-based drilling fluid system to prepare a high-temperature water-based drilling fluid containing GW-1.

[0037] Specifically, the high-temperature water-based drilling fluid comprises the following components by weight: 100 parts water; Eight portions of GW-1 prepared in Example 1; 2.5 parts of sulfonated tannin, a high-temperature viscosity reducer; 3.5 parts of sulfonated phenolic resin, an anti-high temperature filtration loss reducer; 1.5 parts graphite lubricant; 0.3 parts of sodium sulfite, a high-temperature protective agent; pH adjuster sodium hydroxide 0.2 parts.

[0038] In the preparation process, water is first added to a stirring container, and under stirring conditions, high-temperature viscosity reducer sulfonated tannin, high-temperature filtration loss reducer sulfonated phenolic resin, lubricant graphite, high-temperature protective agent sodium sulfite, and pH adjuster sodium hydroxide are added in sequence. The mixture is stirred continuously to ensure that each component is fully dispersed. Then, the phase change microcapsules (GW-1) prepared in Example 1 are added, and the mixture is stirred until the phase change microcapsules are uniformly dispersed in the drilling fluid system to obtain a high-temperature water-based drilling fluid containing phase change microcapsules.

[0039] Application Example 2 The difference from Application Example 1 is that the temperature-controlling additive used in Example 1 was replaced with GW-2 prepared in Example 2. All other preparation conditions and operating procedures were the same as in Example 1.

[0040] Comparative Example 1: Blank water-based drilling fluid.

[0041] Specifically, the blank water-based drilling fluid comprises the following components by weight: 100 parts water; 2.5 parts of sulfonated tannin, a high-temperature viscosity reducer; 3.5 parts of sulfonated phenolic resin, an anti-high temperature filtration loss reducer; 1.5 parts graphite lubricant; 0.3 parts of sodium sulfite, a high-temperature protective agent; pH adjuster sodium hydroxide 0.2 parts.

[0042] In the preparation process, water is first added to a stirring container. Under stirring conditions, high-temperature viscosity reducer sulfonated tannin, high-temperature filtration loss reducer sulfonated phenolic resin, lubricant graphite, high-temperature protective agent sodium sulfite, and pH adjuster sodium hydroxide are added in sequence. The mixture is stirred continuously to fully disperse the components and obtain blank water-based drilling fluid.

[0043] Comparative Example 2: Reduce the high-temperature water-based drilling fluid of GW-1.

[0044] The difference from Application Example 1 is that 8 parts of GW-1 added to the high-temperature water-based drilling fluid system were replaced with 5 parts, while the other preparation conditions and operating steps were the same as in Application Example 1.

[0045] Comparative Example 3: GW-1 high-temperature water-based drilling fluid was added.

[0046] The difference from Application Example 1 is that 8 parts of GW-1 added to the high-temperature water-based drilling fluid system were replaced with 12 parts, while the other preparation conditions and operating steps were the same as in Application Example 1.

[0047] Test Example 1: Temperature control of different drilling fluids.

[0048] The high-temperature water-based drilling fluids prepared in Application Examples 1-2 and Comparative Examples 1-3 were added to high-temperature and high-pressure reactors, respectively, and then placed in a muffle furnace at 230°C to simulate a high-temperature formation environment. The temperature changes of the application examples and comparative examples over time were recorded. When the temperature of the application examples rose to the phase change temperature of the phase change microcapsules, the core material inside the microcapsules underwent a phase change, absorbing heat and slowing down the temperature rise. The maximum temperature difference between the application examples and the comparative examples without phase change microcapsules at the same time was the temperature decrease. Specific results are shown in Table 1.

[0049] Table 1 Comparison of experimental results for temperature control of different drilling fluids As shown in Table 1, in Comparative Example 1 without phase change microcapsules, the drilling fluid temperature continued to rise with heating time under 230℃ heating conditions, showing no obvious temperature control effect, indicating that the conventional drilling fluid system lacks an effective heat buffering mechanism. In contrast, Application Examples 1 and 2 with added phase change microcapsules both showed significant temperature rise suppression effects, indicating that the phase change microcapsules prepared in this invention can absorb external heat through phase change after reaching their phase change temperature, reducing the heating rate of the drilling fluid system and achieving heat control under high-temperature environments.

[0050] Specifically, in Application Example 1, after adding GW-1 microcapsules with a phase change temperature of 195℃, the temperature of the drilling fluid system decreased by 26.5℃. Compared with Comparative Example 1 without phase change microcapsules, it showed a significant temperature control effect, indicating that using molten salt as the phase change core material and encapsulating it with an inorganic coating layer can effectively exert the phase change heat absorption effect and improve the high temperature control capability of the drilling fluid system.

[0051] Furthermore, in Application Example 2, GW-2 microcapsules with a phase change temperature of 225°C were used, resulting in a temperature reduction of 14.8°C. Compared to GW-1, GW-2 has a higher phase change temperature, enabling it to initiate the endothermic process at higher temperatures. This demonstrates that by adjusting the composition of the molten salt core material, the phase change temperature can be controlled, making the phase change microcapsules suitable for high-temperature drilling environments in different temperature ranges.

[0052] Furthermore, by comparing the temperature control effects of different amounts of phase change microcapsules, it was found that in Comparative Example 2, when the amount of GW-1 added was reduced to 5 parts, the temperature reduction decreased from 26.5℃ in Application Example 1 to 16.5℃; while in Comparative Example 3, when the amount of GW-1 added was increased to 12 parts, the temperature reduction increased to 34.6℃. These results indicate that the amount of phase change microcapsules added has a significant impact on the temperature control effect of the drilling fluid system. As the amount of phase change microcapsules added increases, the content of phase change materials that can participate in phase change heat absorption in the system increases, thereby improving the heat absorption capacity of the drilling fluid.

[0053] Example 3 At room temperature, 10 g of molten salt (composed of lithium nitrate and halide salt in a mass ratio of 95:5) and 0.6 g of Tween-40 were added to 20 mL of deionized water and stirred at 300 rpm for 20 minutes to obtain an aqueous phase. 5 g of Span-80 was added to 40 mL of liquid paraffin and stirred thoroughly at 500 rpm for approximately 30 minutes to obtain an oil phase. The aqueous phase was then added to the oil phase, and the mixture was ultrasonically emulsified for 30 minutes to form a stable W / O emulsion. 8 mL of ethyl silicate was added to a water-in-oil emulsion and stirred for 20 minutes at 800 r / min in a constant temperature water bath at 60°C to form a uniformly dispersed system. Then, ammonia was added dropwise to adjust the pH to 9, and stirring was continued for 12 hours. After the reaction was complete, the product was washed three times alternately with deionized water and anhydrous ethanol. Finally, the product was dried at 120°C to prepare high-temperature water-based drilling fluid phase change microcapsules, denoted as GW-3, with a phase change temperature of 235°C.

[0054] The core material (lithium nitrate and halide salt, mass ratio 95:5), wall material (SiO2), and GW-3 were tested using Fourier transform infrared spectroscopy. The specific steps were as follows: The test samples were dried in a vacuum drying oven at 120℃ for 24 hours to avoid affecting the test results. Then, the treated samples were mixed with dried KBr powder at a ratio of 1:400. The mixture was pressed into thin sheets using a hydraulic press, and the chemical composition of the core material, SiO2, and GW-3 was analyzed at room temperature using Fourier transform infrared spectroscopy, with a scanning wavenumber range of 400–4000 cm⁻¹. -1 .

[0055] Experimental results are as follows Figure 3 As shown. In the spectrum of SiO2, the wavenumber is 799 cm⁻¹. -1 The characteristic peaks at these locations correspond to the symmetrical contraction vibration peaks of Si-O-Si; in the spectrum of the core material, the wavenumber is 1384 cm⁻¹. -1 840cm -1 The peaks are attributed to the antisymmetric stretching vibration and out-of-plane bending vibration of nitrate ions, respectively. The spectrum of GW-3 shows that it retains the characteristic absorption peaks of the core material and SiO2, and no new absorption peaks were detected. This proves that the synthesized GW-3 is composed of the core material and SiO2, and that no chemical reaction has occurred between the two materials. The chemical compatibility is good and the three are physically composite.

[0056] X-ray diffraction was used to analyze the crystal form of the wall material (SiO2) and GW-3. The specific steps were as follows: The pre-dried GW-3 sample powder was placed evenly in the groove of a glass slide and then placed in the X-ray diffractometer for testing. The specific parameters were: target material Cu, test current 30 mA, test voltage 30 kV, scanning angle 10–90°, step size 0.05°, and scanning speed 5°·min. -1 .

[0057] Test results are as follows Figure 4 The standard XRD pattern of the core material (JCPDS 80-0203) is shown in the figure. The results indicate that the diffraction peaks at 24.82°, 32.21°, 35.36°, and 42.41° correspond to the (0 1 2), (1 0 4), (0 0 6), and (1 13) crystal planes of the core material, respectively. The SiO2 pattern shows a broad and short, dome-shaped diffraction peak near 2θ=22°, indicating a lack of good crystal structure. This suggests that the SiO2 synthesized by interfacial polymerization is amorphous, indicating very low crystallinity of the SiO2 shell. Characteristic peaks corresponding to the core material and SiO2 can be found in the GW-3 pattern, proving that the microencapsulation process does not affect the crystal structure of the core material. This further confirms that the GW-3 prepared by interfacial polymerization in this paper is composed of the core material and SiO2, and exhibits good chemical compatibility.

[0058] Test Example 2: The effect of different composite molten salts on phase transition temperature.

[0059] Following the method of Example 3, the mass percentages of lithium nitrate in the molten salts were 70%, 80%, 85%, 90%, and 95%, with the remainder being halide salts. The remaining preparation methods were the same as in Example 3, resulting in the preparation of phase change microcapsules with different phase change core materials.

[0060] Table 2. Comparison of phase transition characteristics of composite molten salts with different lithium nitrate mass percentages. As shown in Table 2, by adjusting the mass ratio of lithium nitrate, a composite molten salt phase change core material with an adjustable phase change temperature in the range of 180~235℃, high latent heat, low supercooling, and no phase separation can be prepared. Furthermore, core materials with corresponding phase change temperatures can be prepared according to the application requirements of drilling fluids at different temperatures.

[0061] Example 4 At room temperature, 10 g of molten salt (composed of lithium nitrate and halide salt in a mass ratio of 95:5), 0.5 g of boron nitride (BN), and 0.6 g of Tween-40 were added to 20 mL of deionized water and stirred at 300 rpm for 20 minutes to obtain an aqueous phase. 5 g of Span-80 was added to 40 mL of liquid paraffin and stirred thoroughly at 500 rpm for approximately 30 minutes to obtain an oil phase. The aqueous phase was then added to the oil phase, and the mixture was ultrasonically emulsified for 30 minutes to form a stable W / O emulsion. 8 mL of ethyl silicate was added to a water-in-oil emulsion and stirred for 20 minutes at 800 r / min in a constant temperature water bath at 60°C to form a uniformly dispersed system. Then, ammonia was added dropwise to adjust the pH to 10, and stirring was continued for 12 hours. After the reaction was complete, the product was washed three times alternately with deionized water and anhydrous ethanol. Finally, the product was dried at 120°C to prepare high-temperature water-based drilling fluid phase change microcapsules, denoted as GW-4, with a phase change temperature of 252°C.

[0062] Test Example 3: The effect of different thermally conductive materials on phase transition temperature.

[0063] During the preparation of phase change microcapsules, a small amount of thermally conductive material (molten salt to thermally conductive material mass ratio of 1:20), namely MgO, BN, and AlN, was added to the aqueous phase to optimize the thermal conductivity of LSPCM. The remaining preparation methods were the same as in Example 4, and the prepared microcapsules were named GW-4-Mg, GW-4-B, and GW-4-Al, respectively.

[0064] The thermal conductivity of phase change microcapsules incorporating different thermally conductive materials was tested using a Hot Disk thermal constant analyzer. After drying under identical conditions at room temperature, the sample powder was loaded into a mold and pressed into tablets using a hydraulic press under the same pressure. The results are shown in Table 3.

[0065] Table 3. Performance comparison of phase change microcapsules prepared in Example 3 with phase change microcapsules with different thermally conductive materials. Table 3 shows that the thermal conductivity of the phase change microcapsules is significantly improved after adding a small amount of thermally conductive material. GW-4-Mg exhibits the lowest thermal conductivity, at only 0.673 W·m. −1 ·K −1 The growth rate was only 28.9%; while GW-4-B had the highest thermal conductivity, reaching 0.891 W·m. −1 ·K −1 The growth rate was 70.6%. Therefore, BN was chosen as the thermal conductive material for the microcapsules.

[0066] Test Example 4: pH optimization during preparation.

[0067] The effect of different pH values ​​during the preparation process on the encapsulation efficiency of phase change microcapsules was tested. The encapsulation efficiency formula is: ; In the formula, δ The coverage ratio of LSPCM is %; A Let g be the initial mass of the LSPCM; a The mass after LSPCM ultrasonic fragmentation is expressed in g.

[0068] like Figure 5 As shown, during the preparation of phase change microcapsules, if the pH is too high, the silicon precursor TEOS added to the system will be difficult to disperse uniformly in the oil phase. Simultaneously, it will rapidly undergo hydrolysis and condensation reactions, generating a large amount of amorphous SiO2 in the oil phase. This results in less SiO2 generated at the oil-water interface, failing to completely coat the precipitated LN, or even directly coating it onto the amorphous SiO2. Consequently, a large amount of molten salt is lost during washing, thus reducing the coating rate of the phase change microcapsules. When the pH is 7, the hydrolysis reaction of TEOS in the system becomes difficult, significantly prolonging the reaction time, and even preventing TEOS from reacting completely, thus reducing the coating rate of the phase change microcapsules. In a weakly alkaline aqueous phase, the added TEOS can directly hydrolyze to form oligomers, serving as a precursor to silica. Due to its amphiphilic nature, it diffuses towards the W / O interface and assembles at the interface. Subsequently, APTMS is added to the system; due to its hydrophilicity, it rapidly penetrates into the core. When the amino groups on APTMS come into contact with water, they ionize into NH3⁺, leading to an increase in the concentration of OH⁻ near the W / O interface. This promotes further hydrolysis and condensation of TEOS and APTMS, forming a silica shell at the oil-water interface. As the thickness of the silica shell increases, it encapsulates the precipitated LN. Therefore, a pH of 8-9 for the aqueous phase is preferred.

[0069] Test Example 5: Core-to-wall ratio optimization.

[0070] In high-temperature deep-well environments, phase change microcapsules need to maintain good mechanical strength to prevent core material leakage. However, an excessively high wall material ratio can negatively impact the microcapsule's thermal storage performance, while a low core material ratio can compromise its strength. Therefore, to prepare microcapsules with both high mechanical strength and good thermal storage performance, this test case optimized the core-to-wall ratio of the phase change microcapsules. Experiments were conducted to test the encapsulation efficiency and shear strength of the phase change microcapsules under different core-to-wall ratios, analyzing the influence of the core-to-wall ratio on these properties.

[0071] The specific experimental steps are as follows: A certain amount of phase change microcapsules are weighed and placed in deionized water. After high-speed shearing, they are washed, filtered, and dried. The remaining mass is weighed. The mass lost before and after shearing is the mass of the core material leaking after the phase change microcapsules break. Dividing this core material loss by the mass of the core material before shearing (the product of the microcapsule mass and the encapsulation rate) yields the mass loss rate at that shearing speed. By conducting the above experiment at different shear rates, the shear strength of the phase change microcapsules is analyzed. The specific calculation method is as follows: ; In the formula, δ The coverage rate is %; B The mass of the LSPCM in the first weighing, in g; b The mass of LSPCM in the second weighing, in g; λ The mass loss rate of LSPCM is %.

[0072] The encapsulation efficiency test results of phase change microcapsules under different core-to-wall ratios are as follows: Figure 6 As shown, the LSPCM exhibits the highest encapsulation rate (51.3%) when the core-to-wall ratio is 2:3, while the lowest (31.7%) is achieved when the core-to-wall ratio is 2:1. Furthermore, the encapsulation rate of the phase change microcapsules initially increases and then decreases with increasing core-to-wall ratio. This is because when the core-to-wall ratio is low, TEOS and APTMS in the system generate a large amount of amorphous SiO2 in the oil phase through hydrolysis and condensation reactions. Consequently, some of the SiO2 generated at the oil-water interface directly encapsulates the amorphous SiO2, forming solid phase change microcapsules. At this point, a large amount of deionized water is consumed, and LN begins to precipitate at the oil-water interface. The remaining small amount of amorphous SiO2 cannot completely encapsulate the newly precipitated LN, resulting in the loss of the core material during the washing process, forming phase change microcapsules with low encapsulation rates. As the core-to-wall ratio increases, the rate of amorphous SiO2 generation during the hydrolysis and condensation of TEOS and APTMS reaches a delicate balance with the precipitation of LN, allowing the SiO2 generated in the system to completely encapsulate the LN core material precipitated at the oil-water interface, thus generating phase change microcapsules with higher encapsulation rates. When the core-to-wall ratio is too high, the SiO2 generated by TEOS and APTMS at the oil-water interface in the system is difficult to completely encapsulate LN, causing the microcapsules to fail to form a dense and complete core-shell structure. At the same time, a large number of water molecules containing LN still exist in the reaction system and are washed away during the washing stage, resulting in a decrease in the encapsulation rate of the generated phase change microcapsules.

[0073] The mass loss rate of phase change microcapsules prepared under different core-to-wall ratios in deionized water at different shear rates is as follows: Figure 7As shown in the figure, as the core-to-wall ratio increases from 1:2 to 2:1, the mass loss rate of the phase change microcapsules gradually increases, indicating a decrease in shear strength. This is because the core-to-wall ratio directly affects the wall thickness and encapsulation efficiency of the phase change microcapsules. When the core-to-wall ratio is 1:2, the phase change microcapsules at 14000 r·min −1 The mass loss rate at a shear rate of 8.43% is due to the excessively high proportion of wall material. This results in better shear strength in the prepared phase change microcapsules, but with less core material, lower encapsulation rate, and poorer heat storage performance, limiting the phase change endothermic effect. When the core-to-wall ratio is 2:1, the phase change microcapsules exhibit better shear strength at 14000 r·min⁻¹. −1 The mass loss rate at the shear rate was 10.16%. This is because an excessively high core-to-wall ratio leads to a thinner wall material and reduced shear strength in the phase change microcapsules, increasing the risk of leakage of the LN core material. Furthermore, a large amount of core material cannot be completely encapsulated and is lost during washing, increasing both the preparation cost and the encapsulation rate of the phase change microcapsules. When the core-to-wall ratio was 1:1 and 2:3, the phase change microcapsules at 14000 r·min⁻¹ exhibited good mass loss. −1 The mass loss rates at the shear rates were 9.28% and 8.98%, respectively, and their shear strengths were similar. Furthermore, from... Figure 3-4 It can be seen that the encapsulation rate of phase change microcapsules with a core-to-wall ratio of 2:3 is 51.3%, which is higher than that with a core-to-wall ratio of 1:1.

[0074] In summary, the phase change microcapsules prepared under the condition of a core-to-wall ratio of 2:3 exhibit both high shear strength and higher encapsulation rate, therefore, a core-to-wall ratio of 2:3 is preferred.

[0075] Example 5 The difference from Example 4 is that 10g of molten salt (lithium nitrate), 0.5g of boron nitride (BN) and 0.6g of Tween-80 were added to 20mL of deionized water, with a core-to-wall ratio of 2:3; ammonia was added dropwise to adjust the pH to 8.5, the phase change microcapsules were designated as GW-5, and the phase change temperature was 255℃.

[0076] Of course, the above description is not intended to limit the present invention, and the present invention is not limited to the examples given above. Any changes, modifications, additions or substitutions made by those skilled in the art within the scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids, characterized in that, Includes the following steps: S1. Molten salt phase change core material and hydrophilic emulsifier are added to deionized water, the pH value is adjusted, and the mixture is mixed to form an aqueous phase containing the molten salt phase change core material; S2 adds a lipophilic emulsifier to the organic phase and mixes them to form an organic phase containing the lipophilic emulsifier; S3 mixes the aqueous phase and the organic phase and emulsifies them to form a water-in-oil emulsion; S4. The wall material is added to the water-in-oil emulsion, and a high-temperature resistant coating layer is formed on the outer surface of the molten salt phase change core material by interfacial polymerization to obtain coated phase change microcapsules. S5 separates, washes, and dries the encapsulated phase change microcapsules to obtain phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids.

2. The method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids according to claim 1, characterized in that, In step S1, the molten salt phase change core material includes one or more of potassium nitrate, sodium nitrate, lithium nitrate, sodium chloride, barium nitrate, sodium sulfate, and halide salts; The hydrophilic emulsifier includes one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, Tween-40, and Tween-80; The mixing conditions are: water bath at 20–50 °C, stirring for 15–30 minutes, and a rotation speed of 200–500 r / min. The mass ratio of the hydrophilic emulsifier to the molten salt phase change core material is 1:15 to 30.

3. The method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids according to claim 1, characterized in that, Step S1 further includes adding a thermally conductive material to the aqueous phase; the thermally conductive material is any one or a mixture of MgO, BN or AlN; the mass ratio of the thermally conductive material to the molten salt is 1:10 to 25.

4. The method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids according to claim 1, characterized in that, In step S2, the organic phase is liquid paraffin or white oil; The lipophilic emulsifier includes one or more of glyceryl monostearate, glyceryl monooleate, Span-40, and Span-80.

5. The method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids according to claim 1, characterized in that, In step S2, the mass ratio of the lipophilic emulsifier to the organic phase is 1:5 to 10; the stirring temperature is 30 to 65°C; the stirring time is 20 to 40 minutes; and the stirring speed is 400 to 600 r / min.

6. The method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids according to claim 1, characterized in that, In step S3, the emulsification conditions are as follows: ultrasonic emulsification in an ultrasonic cleaner for 20–30 minutes, with an emulsification stirring rate of 1000–5000 r·min. -1 .

7. The method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids according to claim 1, characterized in that, In step S4, the wall material is a mixture of silicon source precursors; The reaction was carried out in a constant temperature water bath at 40–70°C, and stirred at a magnetic stirring speed of 500–1000 r / min for 20–30 minutes to form a uniformly dispersed system. The reaction system has a pH of 8–13 and a reaction time of 8–16 h; the pH adjuster used is one or more of ammonia, sodium hydroxide, hydrochloric acid, and triethanolamine.

8. The method for preparing phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids according to claim 1, characterized in that, The silicon source precursor mixture is a mixture of tetraethyl orthosilicate and 3-aminopropyltrimethoxysilane. Through hydrolysis and condensation reactions, a strong and dense silica network is formed, satisfying a core-to-wall ratio of 1:0.5 to 2.

9. The phase change microcapsules for high-temperature and ultra-high-temperature drilling fluid prepared by the method according to any one of claims 1 to 8, characterized in that, It includes a molten salt phase change core material and an inorganic wall material layer covering the outer surface of the molten salt phase change core material, wherein the core material is a high-temperature or ultra-high-temperature phase change core material with adjustable phase change temperature; The phase change microcapsules have a phase change temperature of 180–255°C and a core material encapsulation rate of 50–60%.

10. The application of phase change microcapsules for high-temperature and ultra-high-temperature drilling fluids as described in claim 9 in high-temperature water-based drilling fluids, characterized in that... The drilling fluid includes 5 to 12 parts of the phase change microcapsules; When the phase change microcapsules are added to the drilling fluid system, they undergo phase change and heat absorption when they reach their phase change temperature, thereby reducing the rate of temperature rise in the drilling fluid. The high-temperature and ultra-high-temperature drilling fluids are suitable for downhole environments of 180–255°C.

Citation Information

Patent Citations

  • High-temperature phase-change constant-temperature microcapsule, active temperature-control high-temperature drilling fluid system and preparation and application thereof

    CN111545142A

  • Phase change capsule for cooling drilling fluid as well as preparation method and application of phase change capsule

    CN117701255A